2020
DOI: 10.1186/s13068-020-01817-6
|View full text |Cite
|
Sign up to set email alerts
|

Physiological characterization of a new thermotolerant yeast strain isolated during Brazilian ethanol production, and its application in high-temperature fermentation

Abstract: Background The use of thermotolerant yeast strains can improve the efficiency of ethanol fermentation, allowing fermentation to occur at temperatures higher than 40 °C. This characteristic could benefit traditional bio-ethanol production and allow simultaneous saccharification and fermentation (SSF) of starch or lignocellulosic biomass. Results We identified and characterized the physiology of a new thermotolerant strain (LBGA-01) ab… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 45 publications
1
10
0
2
Order By: Relevance
“…Raghavendran et al [11] report a glycerol concentration of approximately 4 g.L -1 for PE-2 in molasses at 30 °C. Additionally, Prado et al [39] obtained glycerol titters higher than 4.5 g.L -1 for a thermo-tolerant strain grown at 34°C. Further investigations adjusting the composition of our 2SMol medium (e.g., lower salt concentrations) or in different osmotic pressures can potentially result in similar glycerol concentrations, with similar biomass variation, ethanol yields, and viability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Raghavendran et al [11] report a glycerol concentration of approximately 4 g.L -1 for PE-2 in molasses at 30 °C. Additionally, Prado et al [39] obtained glycerol titters higher than 4.5 g.L -1 for a thermo-tolerant strain grown at 34°C. Further investigations adjusting the composition of our 2SMol medium (e.g., lower salt concentrations) or in different osmotic pressures can potentially result in similar glycerol concentrations, with similar biomass variation, ethanol yields, and viability.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the total nitrogen concentrations were 0, 602.7, and 2401.6 mg.L -1 in 0SMol, 2SMol, and 4SMol, respectively. Initially, results for CO2 loss normalized to wet cell mass were plotted as in previous research [11,39]. Normalization ensures the biomass increase/decrease is considered during the evaluation of the results, and there is no over/underestimation of the outcomes [11].…”
Section: Case Study: How Do Nitrogen Concentrations Affect Fed-batch ...mentioning
confidence: 99%
“…As previously stated, the E1G production process in Brazilian mills has the peculiarity of using the Melle-Boinot operation, characterized by fed-batch fermentation cycles with high-density cell recycle. Yeast cells are recycled up to 3 times per day and, between each recycling step, face an acid-wash treatment with sulfuric acid (pH ~ 1.5) that aims to reduce bacterial contamination and flocculation [ 16 , 51 ]. Thus, after linking the GAS1 allele to PE-2 tolerance to growth at low pH, we sought to explore if it is possible to increase tolerance to an acid-wash treatment in a naturally susceptible strain after allele swap (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, for bioethanol production, enzymes used in the enzymatic step should ideally act at temperatures close to those used for yeast fermentation. Another alternative would be to prospect for enzymes that act in a range of 40 °C so that they can be used in association with thermotolerant yeasts [ 57 , 58 , 59 ]. Our qualitative xylanolytic activity assays indicated that HtpXyl has the potential to be efficient in these two described situations.…”
Section: Discussionmentioning
confidence: 99%